A Survey Of Teacher and Student Beliefs in Singapores Polytechnics - Fazilah Mohamed Ismail (TEFLIN, 2002)
Abstract: Language teaching has been focused mainly on teachers classroom actions and behaviours and their effects on learners. It is acknowledged that teacher knowledge and beliefs form the underlying framework guiding a teachers classroom practices. However, not to be ignored are learners beliefs about teaching and learning which influence how they approach learning. Thus, teachers need to be informed about learners beliefs so that they can better understand and manage their teaching as well as their students learning. The purpose of this study is to investigate similarities and differences between teachers and students beliefs. Sixty-two English language teachers and 164 students from the four polytechnics in Singapore participated in the study. Data for this study came from these teachers and students responses to a survey questionnaire designed to elicit information about some aspects of their beliefs. In this paper, we will report on some pedagogically interesting differences in certain areas of teachers and students beliefs (e.g., What constitutes good teachers/learners, why learners fail to learn English). We will also discuss the implications of these differences for language teaching and learning.